Temporal Dynamics of Social Exchange and the Development of Solidarity: “Testing the Waters” Versus “Taking a Leap of Faith”. - Kuwabara, Ko; Sheldon, Oliver (Social Forces, 2012)
In their concerted efforts to unpack the microprocesses that transform repeated exchanges into an exchange relation, exchange theorists have paid little attention to how actors perceive changes and dynamics in exchanges over time. We help fill this gap by studying how temporal patterns of exchange affect the development of cohesion. Some exchange relations develop gradually as actors hedge their bets, making incremental commitments to “test the water” and manage the risks of exchange (incremental exchange). Other relations settle quickly into full commitment as actors take “leaps of faith” in each other (constant exchange). Do these patterns result in different levels of bonding? We examined this question across a series of two laboratory studies and a vignette survey that manipulated two dimensions of repeated exchange: resource level (how much actors exchange in each interaction) and frequency (how often actors exchange). In each study, participants played or imagined a series of social exchange tasks with a fixed partner. Results show that exchanging incrementally in resource level promotes cohesion, but exchanging incrementally in frequency undermines it. These findings affirm the importance of exchange frequency for cohesion, but demonstrate an opposite effect of resource level: compared to exchanging constant and full levels, exchanging incremental levels of resources creates more cohesion, even while resulting in lower instrumental benefits.